Development of IoT Monitoring with Solar Tracking System for Multi-Purpose Building - Chew Cheng Wah; Hamidon, Nuramidah; Mohd Arif Rosli; Mariah Awang (Journal of Advanced Industrial Technology and Application, 2025)
This paper discusses the development of an Internet of Things (IoT)-based solar tracking and monitoring system designed to enhance energy efficiency in multipurpose buildings. To optimize solar energy absorption throughout the day, a photovoltaic panel is integrated with a dual-axis solar tracking system. Real-time data, such as voltage, current, and light intensity, is collected and transmitted by an ESP32 microcontroller to a cloud-based platform for remote monitoring and analysis. When compared to a fixed solar panel, a prototype system created and tested under various conditions demonstrated improved energy output. The findings demonstrate that the system facilitates sustainable energy management in building applications, enhances solar efficiency, and reduces the need for human monitoring.